Assessment of Ischemia Modified Albumin and Cardiac Troponin (I) as an Early Diagnostic Markers of Myocardial Ischemia among Patients with Acute Chest Pain - Sadik, Isam; Yagoub, Zuhair; Sayed, Nazra; el nour, Anhar; El Hameed, Mohaed Abide; Abu Saluf, Khalid (Journal of medical and pharmaceutical sciences, 2017)
Cardiac biomarkers have been emphasized as central to the diagnosis and risk stratification strategy for AMI by numerous clinical practice guidelines. Aim: To assess the diagnostic value of Ischemia -modified albumin (IMA) with standard biomarkers (CK-MB, LDH, and AST) troponin I [cTnI] in the early diagnosis of cardiac ischemia. Method: This is cross-sectional study was done 150 with patient’s acute chest pain as target population patients attending to the emergency department of Al Shab Hospital Khartoum. Every case was reviewed by a cardiologist. A clinical diagnosis of ischemia was assigned and correlated with biomarker test results. Results: 127 (84.7%) had myocardial ischemia. Receiver operating characteristic curves demonstrated IMA as highly sensitive but somewhat low specific for the presence of ischemia (area under curve, 0.878; P = .00). With a cut point of 88.16 U/mL, the IMA test had 84.6% sensitivity and 81% specificity for diagnosing ischemia and a negative predictive value of 77.9%. IMA was positive in 127 of 96 patients with electrocardiographic (ECG) evidence of ischemia and 31 of 127 patients with coronary ischemia but negative ECG. Among the same patients, the ECG and cTnI triad had a sensitivity of 64% and 24% respectively. The combination of IMA and ECG increased the sensitivity to (94.5%), and IMA, ECG, cTnI to 95.8%for detecting ischemia. IMA is highly sensitive and has a high negative predictive value, which might improve the usefulness of standard biomarkers of myocardial ischemia. Conclusion: Ischemia Modified Albumin has evaluated as highly sensitive, early diagnostic marker of among acute chest pain patients.